Uma tradição reinventada: o cordel na contemporaneidade - André Magri Ribeiro de Melo (2022)
The objective of this research was to develop a panoramic carthography of Brazilian literature genre Cordel in contemporary times, focusing on the critical and poetic production from 1990 to 2020. Our data are composed of brochures, booklets, books and blog and social network posts. We sought to understand how cordel, an invented tradition of Brazilian Literarure, persists, recreates, and refigures itself, both out of the materiality of printed and digital reading supports. Also, the order of discourse which pervades researchers, poets and editors’ speeches. The archives received qualitative and quantitative treatment based on parameters of Foucauldian discourse analysis, philosophy of difference, History theory, post-literary criticism and Cultural perspectives and History of Reading. The results suggest that the reinvention of cordel is associated within the scope of institutional discourses that exert a productive force on this process, taking it into an interdisciplinary transit between some fields of knowledge and to the use of historical and historiographical concepts and procedures of interpretation that denaturalize and situate it this process in time. The analysis of the editing and printing components indicated the progressive refinement of cordel publishing in the last decades, signaled by the multiplicity of sophisticated supports, graphic-visual projects, editorial paratexts, types of paper, composition, illustration and printing techniques, circulation, dissemination, and insertion of cordeis in different literary fields and events contexts. The poets mostly quoted by legitimated literary instances are white men, supposedly heterosexual, living in capitals or other large cities, over 45 years age, mainly. As for the selected poems, the majority were written by women, it was observed their critical views against regimes of truth which support the regional and traditional cordel literary culture. Especially noticed throughout the narratives permeated by cultures and subjects that are stereotyped and dehumanized, such as women, transvestites, homosexuals, black people and black-Brazilian religions. The research shows that cordel is an archive of secular forms, expressions and imaginaries, and a territory of contemporary forces and their untimeliness, always open to reinvention and displacement, as well. It is the result of historical and human experiences whoever writes it, recites it, reads/listens to it, edits it, researches it.